Analysis of CIC‐associated CpG island methylation in oligoastrocytoma. Issue 7 (29th October 2013) - Sahm, F.; Lass, U.; Herold‐Mende, C.; von Deimling, A.; Hartmann, C.; Mueller, W.
Abstract : Aims: Combined deletion of the whole chromosomal arms 1p and 19q is a frequent event in oligodendroglial tumours. Recent identification of recurrent mutations in CIC on 19q and FUBP1 on 1p and their mutational patterns suggest a loss of function of the respective proteins. Surprisingly, oligoastrocytomas harbouring identical genetic characteristics regarding 1p/19q codeletion and frequent IDH1/2 mutations have been shown to carry CIC mutations in a significantly lower number of cases. The present study investigates whether epigenetic modification may result in silencing of CIC . Methods: As IDH1/2 mutation‐mediated DNA hypermethylation is a prominent feature of these tumours, we analysed a set of CIC wild‐type oligoastrocytomas and other diffuse gliomas with regard to 1p/19q status for presence of CIC ‐associated CpG island methylation by methylation‐specific PCR. Results: Both methylation‐specific PCR and subsequent bisulphite‐sequencing of selected cases revealed an unmethylated status in all samples. Conclusion: Despite the hypermethylator phenotype in IDH1/2 mutant tumours and recent detection of gene silencing particularly on retained alleles in oligodendroglial tumours, hypermethylation of CIC ‐associated CpG islands does not provide an alternative mechanism of functional CIC protein abrogation.